A COMPARATIVE STUDY ON NEUROMOTOR DEVELOPMENT IN TWINS - Bogdan A. ANTOHE (Editura Universitatii Transilvania din Brasov, 2018)
Twins are a valuable source of observation, being considered a key instrument in scientific fields such as genetics, biology, or psychology. The literature suggests that the hereditary and environmental influences can be assessed by comparing twin partners. In this paper we have proposed to demonstrate the existence of differences in the neuromotor development of couples of monozygotic and dizygotic twins. In order to follow the infants' evolution, we used the Peabody motor development scale, consisting of 6 subtests targeting archaic reflexes, locomotion, stationing, object manipulation, catching and visual-motor integration. Children were evaluated every month until the age of 1 year. The results obtained show that there are differences between monozygotic and dizygotic twins, which are highlighted by the development stages.